1997
DOI: 10.1016/s0014-5793(97)01355-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mechanisms and rates of free radical scavenging by carotenoid antioxidants

Abstract: The comparative mechanisms and relative rates of nitrogen dioxide (N0 2 "), thiyl (RS') and sulphonyl (RS0 2 ') radical scavenging by the carotenoid antioxidants lycopene, lutein, zeaxanthin, astaxanthin and canthaxanthin have been determined by pulse radiolysis. All the carotenoids under study react with the N0 2 " radical via electron transfer to generate the carotenoid radical cation (Car' + ). In marked contrast the glutathione and 2-mercaptoethanol thiyl radicals react via a radical addition process to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
161
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(170 citation statements)
references
References 42 publications
5
161
1
3
Order By: Relevance
“…Binding of lycopene or β-carotene to other RNS, such as nitrogen dioxide (Bohm et al, 1995, Kikugawa et al, 1997 has been reported previously, though the nature of the carotenoid-ROS/RNS reaction is dependent on the type of radical species involved (Mortensen et al, 1997).…”
Section: Discussionmentioning
confidence: 79%
“…Binding of lycopene or β-carotene to other RNS, such as nitrogen dioxide (Bohm et al, 1995, Kikugawa et al, 1997 has been reported previously, though the nature of the carotenoid-ROS/RNS reaction is dependent on the type of radical species involved (Mortensen et al, 1997).…”
Section: Discussionmentioning
confidence: 79%
“…The antioxidant properties of tomato-derived lycopene are well known [Di Mascio et al, 1989;Mortensen et al, 1997]. Lycopene has been shown to reduce intracellular levels of hydrogen peroxide via dichlorofluorescein fluorescence assays in MCF-7 cells [Ben-Dor et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms and rate of scavenging of free radicals by carotenoids in solution is strongly dependent on the nature of ROS itself (37). ␤-Carotene is very reactive to peroxy radicals but much less so to hydroxyl radical and superoxide (38).…”
Section: Effect Of Carotenoids On H2o2-induced Mrna Expression and Prmentioning
confidence: 99%